Управління персоналом вищого навчального закладу в умовах радикальних трансформацій сучасної освіти: концептуальний аспект - Ганак, Міхал (My University, 2018)
Виокремлюються особливості роботи з персоналом у ВНЗ в умовах сучасної освіти радикальних трансформацій. Обґрунтовуються положення щодо подальшої демократизації вузівського життя, автономізації ВНЗ, розширення самоуправлінських засад, які вимагають принципових змін і менеджменту персоналу у вищій школі. The peculiarities of working with personnel in higher education institutions in the conditions of modern education of radical transformations are highlighted. The provisions on the further democratization of university life, the autonomy of higher education institutions, the expansion of self-management principles, which require fundamental changes and personnel management in higher education, are substantiated.
Keywords: управління персоналом; personnel management; education; сучасна освіта; personnel management; personnel management; personnel management; personnel management